2092. How Long Should You Delay Insertion of a Long-Term Central Venous Catheter (LTCVC) in Patients with Candida Bloodstream Infection (CBSI)?. (26th November 2018) - Kagan, Evgenia; Jakubowski, Robert; Puri, Shruti; Nolte, Frederick; Salgado, Cassandra
Abstract: Background: Guidelines suggest that among patients with candidemia, placement of an LTCVC, often needed for treatment, can proceed when "additional blood cultures show no growth" but the timeframe is not well defined. There is theoretical risk of relapsed CBSI after therapy if yeast are still circulating in the blood and adhere to the LTCVC. We sought to determine the blood culture time to detection (TTD) for candida to identify a timeframe for LTCVC insertion that would mitigate risk for relapsed CBSI. Methods: We conducted a retrospective cohort study of all positive (+) blood cultures for Candida species (albicans, glabrata, tropicalis, parapsilosis, dubliniensis, krusei, and lusitaniae ) isolated from August 1, 2013–December 31, 2017. Data were retrieved from the microbiology laboratory and the BD BACTEC™ blood culture system was used. TTD was recorded for each (+) blood culture in hours and the mean TTD was calculated by species. Results: One hundred and twenty-eight blood cultures were (+) for Candida species . C . glabrata was the most common species isolated, followed by C . albicans and C . parapsilosis . Overall, the mean TTD was 43 hours (range 7.1–117.7 hours); 19.5% were positive within 24 hours, 67.2% within 48 hours, and 86.7% within 72 hours, and none required more than 120 hours (table). Conclusion: Among patients with candidemia, the majority of blood cultures were positive within 72 hours after inoculation and all were positive within 120 hours; however, among the three most common species, 16.3% required more than 72 hours. Waiting 120 hours before insertion of a LTVC should mitigate risk for relapsed CBSI Disclosures: All authors: No reported disclosures.